Factors in studying employment for persons with disability : how the picture can change - Altman, Barbara Mandell (Research in social science and disability ;, 2017)
The current literature regarding employment among persons with disabilities produces research results dependent on definitions of work disability, the discipline within which research takes places, the model or paradigm of disability in which the research is framed, the methodology and measures used and the cultural context in which employment occurs. This volume seeks to address those factors which have made describing, predicting and examining the work experience of a person with a disability both different and difficult. Contributors examine less frequently anaylzed aspects of employment for persons with disabilities, and offer a variety of approaches to the conceptualization of work, how they differ across cultures, organizations, and types of disability. Topics covered include examination of range of contextual framing of employment for those with disabilities, well-being, the impact of gender, poverty and education and the collection concludes by examining the future of employment developments and trends and the impacts on inclusion of people with disabilities in the paid workforce.